THE EFFECT OF MAHKOTA DEWA (PHALERIA MACROCARPA) (SCHEFF.) FRUIT PERICARP EXTRACT ON INOS IN MICE COLON INTERMITTENTLY-INDUCED BY DEXTRAN SODIUM SULFATE - KUSMARDI, K; ESTUNINGTYAS, A; SHAVERA, D; TEDJO, A; PRIOSOERYANTO, BP (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: The objective of this research was to investigate the anti-inflammatory effect of Mahkota Dewa fruit pericarp extract (Phaleria macrocarpa) on inducible nitric oxide synthase (iNOS) in mice colon induced by dextran sodium sulfate (DSS). Method: The simplisia of P. macrocarpa pericarp was weighed (1000 g) and extracted by maceration process. The total yield of the ethanolic extract was 26.43%. Phytochemical screening was carried out for the detection of the phytoconstituents by simple qualitative methods. The anti-inflammatory activity was performed by DSS-induced colitis model through assessment of hematoxylin-eosin staining and expression of iNOS by immunohistochemistry assay at four different doses, i.e., 650, 1250, 2500, and 5000 mg/kg. Swiss Webster male mice weighing 25-30 g were used for the study. Results: Inflammation score in dose 625, 1250, 2500, and 5000 mg/kg were 1.63, 1.43, 1.32, and 2.20, respectively. This result is significantly different (p=0.008) with DSS group that was 4.37. The results of iNOS optical density score in dose 625, 1250, 2500, and 5000 mg/kg were 1.21, 1.119, 1.22, and 1.37, respectively. This result was significantly different (p=0.000) with DSS group that was 2.24. Conclusion: Pericarp extract of P. macrocarpa fruit exhibited anti-inflammatory activity in the experimental model shown by suppressing the expression of inflammatory cell and iNOS.